2011
DOI: 10.1002/jclp.20829
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stress and coping risk and protective factors associated with changes in adjustment to caring for an adult with mental illness

Abstract: There is a paucity of theory guided longitudinal research into how carers of an adult with mental illness adapt to caregiving. This study examined changes in carer adjustment over 12 months and identified risk and protective factors using stress/coping theory. Eighty-seven carers completed questionnaires at Time 1 and 12 months later (Time 2). The risk/protective factors were background variables, coping resources, appraisals, and coping strategies. Adjustment outcomes were stable over 12 months. Stress/coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 82 publications
3
26
0
Order By: Relevance
“…Benefit finding was above the average for the measure (M = 2.27, SD = 0.39) and close to the reported score by caregivers in previous caregiver research (M = 1.19, SD = 0.50; (Mackay and Pakenham, 2011). Social support was reported by caregivers as being available more than 'Some of the time' (M = 3.07, SD = 1.00) and optimism levels were above the average for the scale (M = 2.82, SD = 0.70).…”
Section: Preliminary Analysissupporting
confidence: 85%
See 2 more Smart Citations
“…Benefit finding was above the average for the measure (M = 2.27, SD = 0.39) and close to the reported score by caregivers in previous caregiver research (M = 1.19, SD = 0.50; (Mackay and Pakenham, 2011). Social support was reported by caregivers as being available more than 'Some of the time' (M = 3.07, SD = 1.00) and optimism levels were above the average for the scale (M = 2.82, SD = 0.70).…”
Section: Preliminary Analysissupporting
confidence: 85%
“…Benefit finding was measured using the Stress Related Growth Scale (SRGS; Park and Fenster, 2004,) which has been used previously in caregivers (Mackay and Pakenham, 2011).…”
Section: Benefit Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Seoul, a study with 252 elderly ladies evaluated if optimism would be related with the subjective wellbeing and the meaning of life, observing that the more optimist elderly tend to give greater meaning to life, which contributes to increase the subjective wellbeing (24) . In context of care provided to the elderly, the variable optimism has shown positive effect on the negative aspects produced by the overload of daily care, among which is the stress (25) . In the studies referenced, it is observed that both optimism and stress present scores that vary depending on the context and on the population studied, and both variables may be influenced by environmental and cultural elements.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies have shown that optimism is an effective measure for reduction of stress in different scenarios of evaluation (23,25) . In this study it was also found that optimism reduces stress in elderlies that care for elderlies and live with children.…”
Section: Discussionmentioning
confidence: 99%